2018
DOI: 10.1080/13588265.2018.1472722
|View full text |Cite
|
Sign up to set email alerts
|

Occupant injury risk assessment and protective measures in frontal collision of a bus

Abstract: Newcastle Upon Tyne, NE1 7RU, UK; +44 1912086197; newrail@newcastle.ac.uk. Dr. Qian PENG is an associate professor of School of Mechanical and Automotive Engineering, Xiamen University of Technology. Main research interests include crashworthiness, biomechanics and lightweight. He carries out research on China Project to improve vehicle safety. Tingting SUN is a postgraduate student of Vehicle Engineering, School of Mechanical and Automotive Engineering, Xiamen University of Technology, majoring in crashworthi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Over the past decades, many essential research achievements have been made [10][11][12]. For instance, children's anthropomorphic test devices (ATDs), with their respective finite element models, were proposed as injury assessment tools to evaluate their injuries in traffic accidents to evaluate the effectiveness of child restraint systems, such as child safety seats and booster seats [13].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, many essential research achievements have been made [10][11][12]. For instance, children's anthropomorphic test devices (ATDs), with their respective finite element models, were proposed as injury assessment tools to evaluate their injuries in traffic accidents to evaluate the effectiveness of child restraint systems, such as child safety seats and booster seats [13].…”
Section: Introductionmentioning
confidence: 99%
“…Each sample has n parameters to be evaluated (j = 1, 2, Á Á Á, n). Step 2: The construction function of normalization was defined as shown in equation (14).…”
Section: Optimization Methodsmentioning
confidence: 99%
“…The protective effects of three-point safety belts for child occupants are significantly better than those of two-point safety belts. 13 Peng et al 14 indicated that a three-point safety belt can effectively limit the movement of occupant and protect the head from impacts experienced when an occupant uses a two-point safety belt only. However, three-point safety belts are unable to effectively protect the child occupants with the non-standard sitting postures, and even cause serious or fatal injury.…”
Section: Introductionmentioning
confidence: 99%